ECONOMY AND PRICE DYNAMICS: MANAGING INFLATION UNDER ECONOMIC UNCERTAINTY - Babayeva Sabinabonu Davronbek qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores the multifaceted nature of inflation and its macroeconomic implications. It identifies and analyzes the primary factors contributing to inflation, including monetary expansion, fiscal policy, demand and supply imbalances, production costs, exchange rate volatility, and inflation expectations. The study emphasizes how these determinants interact within the economic system and evaluates the role of central banks and governments in maintaining price stability. By considering both domestic and international contexts, the paper highlights the importance of a coordinated policy approach to ensure sustainable economic development and macroeconomic equilibrium.